PENGARUH BRAND TRUST DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN AIR MINERAL AQUA (Studi Kasus di Kecamatan Padalarang) - Nita Triana; Aldy Santo Hegiarto (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
This study aims to examine the influence of brand trust and price on consumers' purchasing decisions of Aqua bottled water in the Padalarang District. The research was motivated by a decline in Aqua’s market share in recent years, driven by growing competition and social issues that have shaped consumer perceptions. A quantitative method with a case study approach was employed, involving 100 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed using multiple linear regression with the help of SPSS version 30. The results indicate that both brand trust and price significantly affect purchasing decisions, both partially and simultaneously. Brand trust had a positive effect with a coefficient of 0.182, while price showed a stronger influence with a coefficient of 0.342. The correlation coefficient revealed a strong relationship between the independent and dependent variables. Therefore, the company should enhance brand trust and implement competitive pricing strategies to maintain consumer loyalty amid intense market competition.